FARMER PARTICIPATORY RESEARCH FOR DESIGN AND DELIVERY OF SITUATION SPECIFIC POTATO PRODUCTION TECHNOLOGY IN MEGHALYA - Kumar, Shantanu; Sah, Uma; Deka, C; Baishya, L. K.; Pandey, N. K; Singh, P. H.; Pandey, S. K (Potato Journal, 2013)
Farmer Participatory Research (FPR) approach was utilized to understand the prevailing potato production system, technological gap in adoption of improved potato production technologies and analysis of problems causing low yield of potato in Meghalya state of India. Three important interventions, namely, refinement of farmers’ traditional method of potato planting, assessment of TPS technology and late blight management in low land production situation were implemented in on-farm trials on 30, 50 and 20 farmers’ fields, respectively during 2004-05 and 2005-06. The study revealed that the refined method of potato planting was comparable with the recommended method in terms of yield and economics. TPS technology was found a potential alternative to mitigate the problem on non-availability of quality seed. Under lowland production, management of late blight could be done effectively by one prophylactic spray of mancozeb and one spray of metalaxyl.